(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The emergence of economic units and the innovation of new products is one of the most important challenges in the competition market, and therefore economic units must seek to keep pace with the developments that are taking place at the moment, through the continuous development of systems and methods in cost management of processing chains, which contribute to finding the important pillars on which economic units depend to achieve their goals and maximize their benefits. The research shows the impact of the Corona pandemic on supply chains and their impact on the cost of production in those economic units.Wasit textile and sewing factory – Selecting Iraq as a practical case, we have drawn some conclusions, the most important of which is that the COVID-19 pandemic has had an impact on the production costs of Iraqi economic entities.